PENERAPAN MEDIA VIDEO ANIMASI UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA MATERI TEKANAN ZAT CAIR - Eka Amanda Febriani; Dyah Astriani; Ahmad Qosyim (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
The purpose of this study was to increase students' motivation and learning outcomes on the material of liquid pressure using animated video media. This research was a pre-experimental design research with the design of "One Group Pretest Posttest Design". The research subjects were students of class VIIIA at SMP Negeri 58 Surabaya. The results showed that students' learning motivation increased from the initial motivation of 74.22% in the strong category to the final motivation of 85.72% in the very strong category. N-Gain test student learning outcomes obtained 0.81 in the high category. Student response to the learning of liquid pressure material using animated video media obtained a positive response of 96.5% in a very strong predicate. Based on these results, it showed that the application of animated video media on liquid pressure material can increase student motivation and learning outcomes.